Organization of sorting and surgery of wounds with soft tissue defects during the joint force surgery - Khomenko, I. P.; Lurin, I. A.; Korol, S. O.; Shapovalov, V. Yu.; Hrebennikov, K. O.; Halushka, A. M.; Tertyshnyi, S. V.; Matviichuk, B. V. (Journal of Education, Health and Sport, 2020)
Introduction. The experience of providing medical care during the Anti-terrorist operation in eastern Ukraine showed that in the structure of modern combat surgical trauma gunshot wounds with soft tissue defects are between 64.9-68.2%, of which 36.4-37.5% are small and medium, 28.5-30.7% are large and very large defects. Aim: To improve the results of providing surgical care to the wounded with soft tissue defects by introducing a variety of surgical tactics of wound closure to the medical care levels. Material and Methods. The total array of the study was 2537 wounded with shrapnel, bullet and mine injuries from April 2014 to September 2018. The determination of surgical tactics for closing soft tissue defects was performed at the basis of metric classification taking into account the area, volume and anatomical areas of the lesion. Results. The combination of metric characteristics of wound defects by area, volume with localization of wounds in a single classification allowed the offer of a comprehensive approach to sorting the wounded at the level of medical care and to determine further surgical tactics to close soft tissue defects. In accordance with the sorting and evacuation purposes, the wounded with gunshot wounds to the foot and hand (third zone of injury) were treated in specialised centres to the fourth level of medical care. In the case of medium and large wounds of the thigh, leg, shoulder and forearm, medical care was provided at the second and third levels. And in the case of large and very large wounds of the specified localisation was provided in specialised clinics of the fourth level. Conclusions. The introduction of differentiated surgical tactics in the wounded with soft tissue defects at the levels of medical care has improved functional results: increase the proportion of good from 46.9% to 53.7%, reduce the relative number of unsatisfactory from 18.8% to 11, 6%.